The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ijms24043367
|View full text |Cite
|
Sign up to set email alerts
|

AICAR Ameliorates Non-Alcoholic Fatty Liver Disease via Modulation of the HGF/NF-κB/SNARK Signaling Pathway and Restores Mitochondrial and Endoplasmic Reticular Impairments in High-Fat Diet-Fed Rats

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a global health problem characterized by altered lipid and redox homeostasis, mitochondrial dysfunction, and endoplasmic reticulum (ER) stress. The AMP-dependent kinase (AMPK) agonist 5-aminoimidazole-4-carboxamide ribonucleoside (AICAR) has been shown to improve the outcome of NAFLD in the context of AMPK activation, yet the underlying molecular mechanism remains obscure. This study investigated the potential mechanism(s) of AICAR to attenuate NAFLD by exploring AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…Several studies underscore the role of AMPK activation in improving hepatic steatosis by suppressing ER stress. For example, the AMPK activator AICAR has been shown to alleviate NAFLD by modulating inflammation and ER stress in HFD‐fed rats (Zineldeen et al, 2023). Pyun et al (2021) reported that kynurenic acid attenuates hepatic steatosis through AMPK‐mediated suppression of ER stress in HFD‐fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies underscore the role of AMPK activation in improving hepatic steatosis by suppressing ER stress. For example, the AMPK activator AICAR has been shown to alleviate NAFLD by modulating inflammation and ER stress in HFD‐fed rats (Zineldeen et al, 2023). Pyun et al (2021) reported that kynurenic acid attenuates hepatic steatosis through AMPK‐mediated suppression of ER stress in HFD‐fed mice.…”
Section: Discussionmentioning
confidence: 99%